2016
DOI: 10.1016/j.jneumeth.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Rapid intranasal delivery of chloramphenicol acetyltransferase in the active form to different brain regions as a model for enzyme therapy in the CNS

Abstract: Background The blood brain barrier (BBB) is critical for maintaining central nervous system (CNS) homeostasis by restricting entry of potentially toxic substances. However, the BBB is a major obstacle in the treatment of neurotoxicity and neurological disorders due to the restrictive nature of the barrier to many medications. Intranasal delivery of active enzymes to the brain has therapeutic potential for the treatment of numerous CNS enzyme deficiency disorders and CNS toxicity caused by chemical threat agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Indeed, intranasal administration of obidoxime contributed to a reduction of brain damage and death of rats after poisoning by paraoxon [37]. Also, aerosolized butyrylcholinesterase, as a bioscavenger, was successful for protection of macaque lungs against volatile OPs [38]; rapid intranasal delivery of enzymes to the brain indicates that this route could be used for protection of CNS against toxicants [39], including OPs. Our present results validate the intranasal brain delivery approach using cationic liposome as drug carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, intranasal administration of obidoxime contributed to a reduction of brain damage and death of rats after poisoning by paraoxon [37]. Also, aerosolized butyrylcholinesterase, as a bioscavenger, was successful for protection of macaque lungs against volatile OPs [38]; rapid intranasal delivery of enzymes to the brain indicates that this route could be used for protection of CNS against toxicants [39], including OPs. Our present results validate the intranasal brain delivery approach using cationic liposome as drug carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Another route to enhance protein-loaded nanoparticle delivery to the brain is nasal delivery of drugs into the brain (Lin et al, 2016;Lochhead & Thorne, 2012). This method is less invasive than direct injection, but has many specific requirements for use as a viable delivery method (Appu, Arun, Krishnan, Moffett, & Namboodiri, 2016). Like direct injec tion, nasal delivery has the advantage of skipping first past clearance and can lead to distribution of the therapeutic to various CNS regions via access through the olfactory bulb and brainstem.…”
Section: Nanoparticle-based Deliverymentioning
confidence: 99%
“…Like direct injec tion, nasal delivery has the advantage of skipping first past clearance and can lead to distribution of the therapeutic to various CNS regions via access through the olfactory bulb and brainstem. This is exemplified by delivery of chloramphenicol acetyltransferase to various parts of the brain (Appu et al, 2016). When coupled with matrix metalloproteinase-9 (MMP-9), a molecule known to permeabilize the nasal epithelium, delivery was increased twofold to the midbrain and cortex, and~3-fold to the brainstem.…”
Section: Nanoparticle-based Deliverymentioning
confidence: 99%
“…We have recently shown that intranasally administered oximes bypass the BBB and provide an effective method for protecting the brain from organophosphate mediated CNS damage (Krishnan, Arun et al, 2016). We have also shown rapid intranasal delivery of the bacterial enzyme chloramphenicol acetyltransferase in the active form to different brain regions as a model for enzyme therapy in the CNS (Appu, Arun et al, 2016). Different INDD application methods have been reported in the literature but few studies have examined the relative advantages of the different methods.…”
Section: Introductionmentioning
confidence: 99%
“…INDD of therapeutics provides direct nose to brain delivery via the olfactory and trigeminal pathways (Thorne, Pronk et al, 2004b). INDD circumvents first-pass hepatic metabolism (Miller, Ashford et al, 2008), can transport active enzymes (Appu, Arun et al, 2016), rapid onset to the CNS in therapeutic doses (Krishnan, Arun et al, 2016;Yamamoto, Iseki et al, 2001). This approach is particularly advantageous because charged molecules and high molecular weight compounds, which cannot penetrate the BBB can be rapidly delivered to the CNS (Baker and Spencer, 1986).…”
Section: Introductionmentioning
confidence: 99%